2008
DOI: 10.1016/j.mrfmmm.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus (HCMV) and hearing impairment: Infection of fibroblast cells with HCMV induces chromosome breaks at 1q23.3, between loci DFNA7 and DFNA49—Both involved in dominantly inherited, sensorineural, hearing impairment

Abstract: Human cytomegalovirus (HCMV) infection is the most common congenital infection in developed countries and is responsible for a substantial fraction of sensorineural hearing impairment (SNHI) in children. The risk of hearing impairment is associated with viral load in urine and blood collected during the first postnatal month. However, although inner ear abnormalities are observed in some children with HCMV-induced SNHI, the exact mechanism whereby congenital HCMV infection causes hearing impairment is unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
1
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
(45 reference statements)
0
21
1
4
Order By: Relevance
“…Although congenital CMV infection did not induce GJB2 mutation in this study, some previous experiments in vitro indicated that CMV infection did induce genetic damage at 1q23.3, with a breakpoint situated between two hearing impairment loci, DFNA49 and DFNA7 (14). Fortunato et al (17) demonstrated that infection of S-phase human fibroblast cells with CMV resulted in chromosome breaks at positions 1q21 and 1q42; these two chromosomal band locations contain loci involved in dominantly and recessively inherited hearing impairment, respectively.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Although congenital CMV infection did not induce GJB2 mutation in this study, some previous experiments in vitro indicated that CMV infection did induce genetic damage at 1q23.3, with a breakpoint situated between two hearing impairment loci, DFNA49 and DFNA7 (14). Fortunato et al (17) demonstrated that infection of S-phase human fibroblast cells with CMV resulted in chromosome breaks at positions 1q21 and 1q42; these two chromosomal band locations contain loci involved in dominantly and recessively inherited hearing impairment, respectively.…”
Section: Discussioncontrasting
confidence: 73%
“…As genetic factors, the mutations of the gap junction β-2 (GJB2) gene were considered an important cause of SNHL (9)(10)(11)(12). Studies indicate that congenital CMV infection may cause chromosome aberrations, including selective chromosome breakages, chromosome pulverization, premature chromatid condensation, and structural injury to the centrosome (13)(14)(15)(16)(17)(18), e.g., genetic damages on 1q23.3 (14), 1q21, and 1q42 (17). However, whether CMV infection can induce mutations of GJB2 on human chromosome 13q11-q12 remains unclear.…”
mentioning
confidence: 99%
“…NES is associated with cytoplasmic trafficking in NPCs and plays an important role in the distribution and organization of critical cellular factors regulating cell proliferation and differentiation (39,53). Additionally, NES is located at 1q23 (an area that has been shown to be targeted selectively by HCMV) (42). Therefore, the downregulation of NES (and perhaps other neural genes) may be related to the selective effect of HCMV at 1q23.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that HCMV can inflict site-specific chromosomal damage in the form of double-strand breaks (DSBs) (13,30). DSBs can be repaired without error by homology-directed repair (HDR) or by error-prone mechanisms such as nonhomologous end-joining or single-strand annealing (34,42).…”
mentioning
confidence: 99%